Effect of CEO Compensation on Corporate Tax Avoidance (CTA) and Role of Audit Quality as Moderation Variable - Kadarisman Hidayat (University of Merdeka Malang, 2022)
This research aims to investigate the influence of CEO Compensation on Corporate Tax Avoidance (CTA) and examine the role of Audit Quality (AQ) as a moderating variable that can increase the influence of CEO compensation on CTA. This study employed quantitative research by moderated regression analysis (MRA) with the STATA program, and this method used the annual report of firms listed on the Indonesian stock exchange from the 2018-2020 period with a sample of 195 firms. The results showed that CEO compensation influences CTA as measured by DER. That is, the higher CEO compensation made the company can improve CTA. The results of this research also show that Audit Quality (AQ) as a moderation variable is proven empirically able to decrease the influence of CEO compensation on CTA.